Follicular dendritic cell‐secreted protein is decreased in experimental periodontitis concurrently with the increase of interleukin‐17 expression and the Rankl/Opg mRNA ratio. (19th July 2013) - Takahashi, S.; Fukuda, M.; Mitani, A.; Fujimura, T.; Iwamura, Y.; Sato, S.; Kubo, T.; Sugita, Y.; Maeda, H.; Shinomura, T.; Noguchi, T.
<x xml:space="preserve">Abstract</x> Background and Objective T‐helper type 17 (Th17) cells produce interleukin‐17 (IL‐17) and help to protect against inflammation and infection in periodontal disease. Furthermore, while follicular dendritic cell‐secreted protein (FDC‐SP) may be involved in the inflammation of periodontal tissue, the biological role of FDP‐SP in periodontal disease is still unknown. The purpose of the present study was to clarify the expression of IL‐17 and FDC‐SP in experimental periodontitis in rats. Material and Methods Seven‐week‐old male Wistar rats were divided into baseline control, sham and test groups. Experimental periodontitis was induced by placing a ligature in the mesiopalatal area, and untreated rats served as a baseline control group. Morphological changes in alveolar bone were investigated 7, 14 and 28 d after treatment. Expression of the Rankl, osteoprotegerin (Opg) and Il17 genes was analyzed 5 and 7 d after the induction of experimental periodontitis. Results Alveolar bone resorption progressed in the test group for 7 d, but not thereafter. At 5 d after the induction of periodontitis, the Rankl/Opg mRNA ratio and the expression of IL‐17 in the test group were significantly increased compared with the respective values in the baseline control group; however, there were no significant differences between the test and control groups at 7 d. The expression of FDC‐SP was significantly decreased in the test group compared with the baseline control group at 5 and 7 d after the induction of periodontitis, and this value had returned to normal levels at 14 and 28 d. Conclusion These results suggest that both IL‐17 and FDC‐SP could be involved in the inflammatory response, and FDC‐SP in the junctional epithelium might play an important role in the Th17 cell‐related immune response.